2016
DOI: 10.1080/11250003.2016.1172121
|View full text |Cite
|
Sign up to set email alerts
|

Genetic investigation of Italian domestic pigeons increases knowledge about the long-bred history ofColumba livia(Aves: Columbidae)

Abstract: Genetic investigation of Italian domestic pigeons increases knowledge about the long-bred history of Columbalivia (Aves: Columbidae),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 32 publications
0
17
1
Order By: Relevance
“…[ 10 ], Bigi et al . [ 11 ] and Biała et al . [ 12 ] who studied Egyptian, Polish, and Italian pigeon populations, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 10 ], Bigi et al . [ 11 ] and Biała et al . [ 12 ] who studied Egyptian, Polish, and Italian pigeon populations, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The microsatellite is a marker of choice for studying the genetic diversity and relationships among closely related livestock breeds [ 11 , 12 ]. MtDNA of pigeon was used to construct a phylogenic tree for C. livia , Streptopelia , and other related taxa [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Simms 61 (1979) suggested that juveniles homing pigeons lost at the beginning of their training period constituted an 62 important component of feral populations at least in the UK. 63 In Italy, pigeon breeding has been an embedded activity since ancient times especially in Northern and 64 Central regions, where several domestic breeds have been selected (McNeillie 1976;Bigi et al 2016). It 65 can be assumed that these local breeds have mostly contributed to the Italian feral populations, possibly 66 with birds (both dovecote and wild individuals) imported mainly from Egypt (from the range of C. l. gaddi 67 and C. l. schimperi subspecies) and Spain, used in pigeon shooting ranges till the first half of the last 68 century (Ghigi in Toschi 1939).…”
mentioning
confidence: 99%
“…It 65 can be assumed that these local breeds have mostly contributed to the Italian feral populations, possibly 66 with birds (both dovecote and wild individuals) imported mainly from Egypt (from the range of C. l. gaddi 67 and C. l. schimperi subspecies) and Spain, used in pigeon shooting ranges till the first half of the last 68 century (Ghigi in Toschi 1939). 69 In recent years, domestic pigeons have been the subject of several genetic investigations, mainly 70 aimed at understanding their relationships and their geographic origins (Stringham et al 2012;71 Shapiro et al 2013;Biala et al 2015;Bigi et al 2016;Domyan and Shapiro 2017), whereas feral 72 pigeons, on the contrary, received rather less attention. While a number of the above-mentioned 73 studies on domestic breeds actually included one group of feral pigeons in their analyses (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation